Photoexcited charge manipulation in conjugated polymers bearing a Ru(ii) complex catalyst for visible-light CO2 reduction. Issue 37 (20th May 2022) - Nakada, Akinobu; Miyakawa, Ryuichi; Itagaki, Ren; Kato, Kosaku; Takashima, Chinami; Saeki, Akinori; Yamakata, Akira; Abe, Ryu; Nakai, Hiromi; Chang, Ho-Chol
Abstract : Photoexcited charge manipulation was demonstrated by molecular engineering in conjugated polymers, bearing a Ru(ii ) complex as the CO2 reduction photocatalyst. Abstract : Conjugated polymers have emerged as promising candidates for photocatalyst materials. Design principles that maximize the synergy between the conjugated skeleton and catalyst moiety are strongly desired to be established for achieving efficient photocatalysis. Herein, the photoexcited charge manipulation was demonstrated by molecular engineering in conjugated polymers bearing a Ru(ii ) complex as the CO2 reduction photocatalyst. Combinational studies based on ultrafast spectroscopies and theoretical calculations revealed that the introduction of an electron-donating carbazole (Cz) skeleton in the polymer enables enhanced photoexcited charge trapping on the Ru(ii )-complex catalyst moiety. The carbazole-based polymer [Cz-bpyRu] n facilitates CO2 reduction under visible light even longer than 500 nm and exhibited 7- to 15-fold greater activity than those of phenyl (Ph) and benzothiadiazole (Bt) counterparts. The findings of this study thus provide insights into molecular engineering for photoexcited charge manipulation to achieve efficient photocatalysis.